(untitled) - Seuss; Dr. (New York, 1950)
If Gerald McGrew ran the zoo, he'd let all the animals go and fill it with more unusual beasts--a ten-footed lion, an Elephant-Cat, a Mulligatawny, a Tufted Mazurka, and others.
Keywords: Stories in rhyme